Noncoding Y RNAs regulate the levels, subcellular distribution and protein interactions of their Ro60 autoantigen partner. Issue 12 (29th May 2020) - Leng, Yuanyuan; Sim, Soyeong; Magidson, Valentin; Wolin, Sandra L
Abstract: Noncoding Y RNAs are abundant in animal cells and present in many bacteria. These RNAs are bound and stabilized by Ro60, a ring-shaped protein that is a target of autoantibodies in patients with systemic lupus erythematosus. Studies in bacteria revealed that Y RNA tethers Ro60 to a ring-shaped exoribonuclease, forming a double-ringed RNP machine specialized for structured RNA degradation. In addition to functioning as a tether, the bacterial RNA gates access of substrates to the Ro60 cavity. To identify roles for Y RNAs in mammals, we used CRISPR to generate mouse embryonic stem cells lacking one or both of the two murine Y RNAs. Despite reports that animal cell Y RNAs are essential for DNA replication, cells lacking these RNAs divide normally. However, Ro60 levels are reduced, revealing that Y RNA binding is required for Ro60 to accumulate to wild-type levels. Y RNAs regulate the subcellular location of Ro60, since Ro60 is reduced in the cytoplasm and increased in nucleoli when Y RNAs are absent. Last, we show that Y RNAs tether Ro60 to diverse effector proteins to generate specialized RNPs. Together, our data demonstrate that the roles of Y RNAs are intimately connected to that of their Ro60 partner.